Akten zur Auswärtigen Politik der Bundesrepublik Deutschland 1986 - Taschler, Daniela (Akten zur Auswärtigen Politik der Bundesrepublik Deutschland, 2017)
The 370 documents contained in this volume focus on arms control, especially the US-Soviet summit in Reykjavik, and on the dynamics of East-West relations triggered by Gorbachev`s policy of Glasnost. In addition, the documents disclose other milestones in dètente, such as the successful conclusion of the CDE talks in Stockholm, the nuclear disaster in Chernobyl and the bombing of the Berlin disco La Belle.